Os trabalhadores docentes e suas traduções do PROEMI no Espírito Santo - Tavares, Adriana de Cássia Peterlini (2018)
The work presented in this dissertation has as its object the study of the Higher Education Teaching Programam (ProEMI) the program was created in 2009 and established by the opinion CNE/CP nº 11/2009, having as Minister of Education Fernando Haddad its purpose was to contribute to significant changes in public high schools in Brazil and consequently to revert the negative indicators of this stage ob Basic Education, the proposal was a dynamic, participative and continuos process and stimulation tonew forms og organization of the disciplines articulated to integrative activities, from the interrelations among the constituent axes of High School, work, science, technology and culture.This research is derived from the research coordinated by the Center for Studies and Research in Educational Policies(NEPE) of the Federal University of Esípito Santo, “Innonative High School:Working conditions and teacher training”, was real between the years 2013 and 2017, in five randomly chosen high schools in te State of Espírito Santo.Our research is centered on the program in the schools that are part of the marix search. In order to carry out this research the following methodological procedures were questionnaires applied to teachers, interviews with public managers and focus groups with teachers as well a bibliographical and documentary research. As an epistemological basis for the data analysis, we used the “Public Policy Cycle Approach”, elaborated by Stephen Ball et al (1994). From this epistemological perspective, we use the translation concept to base our research hypothesis, which considers that the translation carried out by the teaching staff is based on the translation carried out by the technicians of the State Secretary os Education (SEDU) and may consider that the translation process occurs the translation” of ProEMI. Having as objectives to be unveiled: how were the processes of implantation of ProEMI in the schools researched, the unfoldings occurred in relation to the news forms of teacher’s organization and to investigate how the information transfer by SEDU of the guindance documents and how ProEMI translation was carried out by teaching staff I the five schools surveyed. In the process of conducting the research, there was thw possibility of knowing the dynamics of ProEMI, its interlacing with the curricular guidelines for High School and how the State of Espírito Santo made the program adherence and the processes that constituted tle implantation in the schools surveyed. The analysis of data obtained from the questionnaire completion by the teachers brought important information among them we highlight: predominantly the teacihnh staff of the school’s studies is made up of 69% women, 98% of the Teachers have a bachelor’s degree and 85% have a specialization, 26,5% of the professors teach in the High School between 6 and 10 years, 68% of the teachers who work in the school are bankrupt, 40% of the teachers claimed to follow SEDU’s orientation to join ProEMI,47% of the respondents state, 56% of the teachers satated that ProEMI promoted innovative practices in schools, 49,4% of teachers showed that the program increased the diversity of pedagogical practices, 47,3% of interviwees pointed out that ProEMI brought improvements in the physical and material structure os schools. After analyzing the data, it can be stated that the implantation of ProEM in the five schools studied was based on experiences already developed by teaching staff that with the financial resources received could carry out innovative projects. At the same time, we observe that the lack of continuity of public educational policies causes great losses in relation to the advances achieved by Education.